2016
DOI: 10.1007/s10903-015-0339-1
|View full text |Cite
|
Sign up to set email alerts
|

Park-Use Behavior and Perceptions by Race, Hispanic Origin, and Immigrant Status in Minneapolis, MN: Implications on Park Strategies for Addressing Health Disparities

Abstract: The study examines the connections between minority status, park use behavior, and park-related perceptions using recent survey data from three low-income neighborhoods in Minneapolis, MN. Blacks and foreign-born residents are found to underutilize parks. Blacks, Asians, and American Indians perceive fewer health benefits of parks than whites, including the benefits of parks for providing exercise/relaxation opportunities and family gathering spaces. Foreign-born residents, blacks, and Hispanics perceive great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 18 publications
3
27
0
Order By: Relevance
“…It will be important to address the added constraint that the advent of mobile digital technology [47] places on whether families chose to spend time outdoors for health. Individual-level factors that influence outdoor time in general (including but not limited to time in parks), such as gender [48], income [49], immigration status [50], attitudes about feeling welcome [51], racism [52], family structure [53], and a person's innate motivation to engage in outdoor activities [54], availability of social opportunities, and family rules [55,56], have each been correlated with spending time outdoors. We are interested in better understanding whether the concept of a park visit, versus time in nature, will motivate outdoor behavior.…”
Section: Discussionmentioning
confidence: 99%
“…It will be important to address the added constraint that the advent of mobile digital technology [47] places on whether families chose to spend time outdoors for health. Individual-level factors that influence outdoor time in general (including but not limited to time in parks), such as gender [48], income [49], immigration status [50], attitudes about feeling welcome [51], racism [52], family structure [53], and a person's innate motivation to engage in outdoor activities [54], availability of social opportunities, and family rules [55,56], have each been correlated with spending time outdoors. We are interested in better understanding whether the concept of a park visit, versus time in nature, will motivate outdoor behavior.…”
Section: Discussionmentioning
confidence: 99%
“…We can assume that the effects of ambient exposures are distributed amongst all residents in a given area, as active use does not determine exposure. However, in terms of active use of parks, a growing body of research from the leisure sciences and urban geography attempts to explain whether and why members of certain social groups may either be less likely to visit parks (Das et al, 2017;Finney, 2014;Kabisch and Haase, 2014) or to be less likely to use them for active recreation (Derose et al, 2015). Explanations for differences in park use by race, for example, describe the historical meaning of such spaces for certain groups such as the historical association of open space with lynching, or associations with other types of violence (Agyeman et al, 2016;Finney, 2014).…”
Section: Do All Residents Benefit Equitably From Active Green Space?mentioning
confidence: 99%
“…Moreover, research has shown that underrepresented groups such as African Americans, Hispanics, and foreign-born residents report more unique barriers to park use. These barriers include not feeling welcome and appreciated, cultural and language restrictions, inconvenient program schedules and pricing concerns, poorly maintained facilities, and safety concerns [24]. In the same vein, previous studies have found that limited spatial access to parks, inadequate or poorly maintained facilities, lack of bilingual staff, and perceived safety hazards were some of the biggest concerns regarding park use voiced by racial and ethnic minority groups [25,26,27].…”
Section: Introductionmentioning
confidence: 99%